Estimation of the risk of failure in the water supply as support to the planning and management of water resources - Avilés, Alex; Solera, Abel (Maskana, 2012)
In this study numerical models and stochastic scenarios are used to verify if the water resource systems of the Paute River Basin under the given conditions of infrastructure (storage reservoirs) are capable of meeting the water demand in 30 years from today. The analysis revealed the need to implement a reservoir with a capacity of at least 21 Hm3 in the Tomebamba subbasin, whereas the Pindilig subbasin does not require any storage reservoir. In case the water supply during dry periods ceases below the water demand the implementation of water use restriction measures might be required. The results clearly show the usefulness of used approach and its capacity in generating alternatives in water supply and demand for future conditions. As such the method will be very helpful to decision-makers in defining the most appropriate policies for the planning and management of the water resources.